Between critique and affirmation - Starzyński, Wojciech (Phainomena (Ljubljana), 2025)
The article reconsiders Leopold Blaustein’s philosophy by focusing on his critical stance toward metaphysics. While Witold Płotka interprets Blaustein as a philosopher of metaphysical neutrality, I argue that Blaustein should rather be seen as a critic of metaphysical idealism who nonetheless develops a minimal and functional form of metaphysical reflection. This reflection is grounded not in ontological assumptions, but in the implicit meaningfulness of anthropological experience. The article examines four domains—intentionality, humanistic psychology, aesthetics, and education—and includes a final boundary-case analysis of religious spirituality, in order to clarify the scope and limits of Blaustein’s functional metaphysics. Drawing on his critique of Ingarden and his own educational writings, I argue that Blaustein’s philosophy ultimately points toward a non-speculative, yet normatively rich conception of culture and value. His project, although critical of traditional metaphysics, remains open to a constructive transformation of metaphysical thinking rooted in human experience and practical reason.
Keywords: Blaustein; culture; fenomenologija; intencionalnost; intentionality; kultura; metafizika; metaphysics; phenomenology